Service research: past, present and future research agenda - Hasan Evrim Arici; Mehmet Ali Köseoglu; Levent Altinay (Emerald, 2022)
PurposeThis study aims to explore past and present service research and to provide a future research agenda for service researchers by presenting a big picture of the intellectual connections and emerging topics in the discipline.Design/methodology/approachThis study is an empirical analysis of citations and cocitations on a sample of 5,837 articles published in leading service journals (from 1981 to December 2020). Network analysis was adopted to analyze the data. This study is exclusive in conducting the inquiry at the individual publication level, rather than using the normal aggregated author co-citation analysis approach.FindingsThe findings reveal that the main themes of service research centered on customer satisfaction, service quality, service-dominant logic, methodological foundations, market orientation and service encounter. Also clarified is the periphery domain that may become more important in the future (i.e. technology). The findings also present anchor points for conceptual framing and conceptual development – five main themes that are momentous to navigate theory discovery and justification in the knowledge domain.Research limitations/implicationsIt calls for a more academic effort to evaluate the service research by considering different epistemological paradigms, such as positivism, monologic and hermeneutic, to better understand the process and progress of the discipline.Practical implicationsThrough exploring the transformation of service research into a customer-centric model and technology-based service logic, this study offers possible implications for practitioners and further research areas for service researchers.Originality/valueTo the best of the authors’ knowledge, this study is the first to use a citation, cocitation and network analysis to examine service research published in leading service journals. This study provides a significant contribution to the theory by combining main conceptual areas and interests in the given discipline.
Keywords: Bibliometric analysis; Citation analysis; Co-citation analysis; Service research; Marketing. Distribution of products; HF5410-5417.5; Future agenda; Intellectual structure